Assessing Stress Levels and Coping Strategies in the New Normal among Students of Magsaysay College - Arlyn A. Padilla; Don T. Cahilog; Jelyn S. Sarong; Felix E. Arcilla Jr. (Randwick International of Education and Linguistics Science Journal, 2024)
The primary objective of this study was to assess stress levels and analyze coping strategies among Magsaysay College students. Utilizing a descriptive correlational research design, the study explored the relationship between students' demographic profiles, including age, gender, marital status, year level, family income, and reported stress levels. It also examined the correlation between stress levels and the use of coping strategies. The research concluded that demographic factors do not have a significant impact on stress levels among students and that stress is a ubiquitous challenge for students across different backgrounds. Interestingly, there is a slight negative correlation between family income and stress levels among students; this relationship is not statistically significant. This suggests that students show resilience and do not let the challenges of lower family income escalate their stress levels appreciably. A positive correlation was identified between stress levels and the employment of coping strategies, indicating that students tend to rely more on coping mechanisms as stress levels increase. It was recommended that Magsaysay College’s Guidance Center enhance its mental health support services by providing more resources, educational programs, and online counseling on effective coping strategies. Local Government Unit (LGU) of Magsaysay and other stakeholders are advised to collaborate on community-based support programs and invest in mental health initiatives to bolster the well-being of the students. Such collaborative efforts could significantly contribute to a more supportive learning environment, fostering students' academic success and personal growth.